2016
DOI: 10.3389/fmars.2016.00068
|View full text |Cite
|
Sign up to set email alerts
|

Bioactivity Screening of Microalgae for Antioxidant, Anti-Inflammatory, Anticancer, Anti-Diabetes, and Antibacterial Activities

Abstract: Marine microalgae are considered a potentially new and valuable source of biologically active molecules for applications in the food industry as well as in the pharmaceutical, nutraceutical, and cosmetic sectors. They can be easily cultured, have short generation times and enable an environmentally-friendly approach to drug discovery by overcoming problems associated with the over-utilization of marine resources and the use of destructive collection practices. In this study, 21 diatoms, 7 dinoflagellates, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
244
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 299 publications
(256 citation statements)
references
References 61 publications
9
244
1
2
Order By: Relevance
“…SQDGs have been reported to show inhibitory activity against DNA polymerase, HIV-reverse transcriptase type 1, and platelet-activating factor receptor binding [13,14]. Like digalactosyldiacylglycerols and other monogalacytosyl analogs isolated from microalgae, the SQDG isolated in our study also showed strong NO-inhibition in murine macrophage RAW264.7 cells [15,16], more significant than the trioxilin isolated from the same extract.…”
Section: Introductionmentioning
confidence: 49%
See 1 more Smart Citation
“…SQDGs have been reported to show inhibitory activity against DNA polymerase, HIV-reverse transcriptase type 1, and platelet-activating factor receptor binding [13,14]. Like digalactosyldiacylglycerols and other monogalacytosyl analogs isolated from microalgae, the SQDG isolated in our study also showed strong NO-inhibition in murine macrophage RAW264.7 cells [15,16], more significant than the trioxilin isolated from the same extract.…”
Section: Introductionmentioning
confidence: 49%
“…The two compounds exhibited strong NO-inhibitory activity on RAW264.7 cells. Although dinoflagellates are best known for the toxin producers, they have provided novel structures with biological activity (e.g., anticancer) [16,23]. Furthermore, microalgae including dinoflagellates have the ability to produce diverse metabolites through changes in culture conditions, and might be a promising source for drug discovery.…”
Section: Resultsmentioning
confidence: 99%
“…Considering that stress conditions may enhance the production of bioactive compounds [52], recently Ingebrigtsen et al [53] and Lauritano et al [52] tested the anti-diabetes properties of several microalgae cultured in stressful conditions, using the PTP1B assay (i.e., evaluation of the Protein Tyrosine Phosphatase 1B inhibition). Ingebrigtsen et al [53] tested the less polar fraction of 5 North-Atlantic diatoms (i.e., Attheya longicornis , Chaetoceros socialis , Chaetoceros furcellatus , Skeletonema marinoi and Porosira glacialis ) grown in four different light/temperature conditions: high/low temperatures (ranging from 3.3 to 9 °C) and high/low light irradiance (ranging from 30 to 160 μmol photons m −2 ·s −1 ).…”
Section: Marine Microorganisms With Anti-diabetes Propertiesmentioning
confidence: 99%
“…These results confirmed that culturing conditions are very important in triggering the production of the bioactives of interest. On the other hand, Lauritano et al [52] screened crude extracts of 32 microalgal species (21 diatoms, seven dinoflagellates and four flagellates) grown in three different culturing conditions, i.e., replete medium, and nitrogen- and phosphate-starved media (90 μM NO 3 − for nitrogen-starved and 0.5 μM PO 4 2− for phosphate-starved media). Results did not show active hits for the microalgae cultured in these conditions, including 21 diatom species, thereby indicating that temperature/light stress may be more important than nutrient stress in triggering the production of bioactive compounds that inhibit the PTP1B enzyme associated with type-2 diabetes.…”
Section: Marine Microorganisms With Anti-diabetes Propertiesmentioning
confidence: 99%
“…In the pharmaceutical industries drug candidates with anti-inflammatory, anticancer, and anti-infective activities have been identified [10]. For instance, adenosine from Phaeodactylum tricornutum , can act as an anti-arrhythmic agent for the treatment of tachycardia and the green algal metabolite caulerpin is featured in studies of anti-tuberculos is activities [11,12]. Production of oleaginous microalgae are becoming attractive as alternative sources of biofuels with potential to meet global demand for renewable bioenergy [13].…”
Section: Introductionmentioning
confidence: 99%